2004
DOI: 10.1055/s-2004-821075
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Surgery for Small Cell Lung Cancer - Response to Induction Chemotherapy Predicts Survival

Abstract: Surgery combined with chemotherapy is a therapeutic option in selected patients with SCLC. Pathologic nodal status and response to induction chemotherapy are predictors of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 9 publications
1
17
0
1
Order By: Relevance
“…One Japanese multi-institutional phase II study (JCOG9101) has reported that recurrence after surgery occurred in 43% (26/61) of patients overall, in 29% (10/35) of patients with p-stage I disease, in 50% (4/8) of patients with p-stage II, and in 67% (12/18) of patients with p-stage III, and that the incidence of brain metastasis was 15% (9/61) in patients overall, 11% (4/35) in patients with p-stage I disease, 38% (3/8) in patients with p-stage II, and 11% (2/18) in patients with p-stage III [20]. Another Japanese study showed that relapse after surgery occurred in 34 of 69 (49%) patients who underwent complete resection of SCLC and in 27% (8/30) of patients with p-stage I disease, 58% (7/12) of patients with p-stage II, 69% (18/26) of patients with p-stage III, and 100% (1/1) of patients with p-stage IV [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One Japanese multi-institutional phase II study (JCOG9101) has reported that recurrence after surgery occurred in 43% (26/61) of patients overall, in 29% (10/35) of patients with p-stage I disease, in 50% (4/8) of patients with p-stage II, and in 67% (12/18) of patients with p-stage III, and that the incidence of brain metastasis was 15% (9/61) in patients overall, 11% (4/35) in patients with p-stage I disease, 38% (3/8) in patients with p-stage II, and 11% (2/18) in patients with p-stage III [20]. Another Japanese study showed that relapse after surgery occurred in 34 of 69 (49%) patients who underwent complete resection of SCLC and in 27% (8/30) of patients with p-stage I disease, 58% (7/12) of patients with p-stage II, 69% (18/26) of patients with p-stage III, and 100% (1/1) of patients with p-stage IV [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, use of PCI after combined-modality treatment with surgery for resectable LS-SCLC has not yet been investigated sufficiently. As far as we are aware, only 2 Japanese studies have reported the frequency of brain relapse after surgery for LS-SCLC [19,20]. One Japanese multi-institutional phase II study (JCOG9101) has reported that recurrence after surgery occurred in 43% (26/61) of patients overall, in 29% (10/35) of patients with p-stage I disease, in 50% (4/8) of patients with p-stage II, and in 67% (12/18) of patients with p-stage III, and that the incidence of brain metastasis was 15% (9/61) in patients overall, 11% (4/35) in patients with p-stage I disease, 38% (3/8) in patients with p-stage II, and 11% (2/18) in patients with p-stage III [20].…”
Section: Discussionmentioning
confidence: 99%
“…One Japanese multi-institutional phase II study (JCOG9101) has reported that the overall incidence of BM was 15% (9/61) in patients with surgically resected SCLC, but only 11% (4/35) in patients with p-stage I disease compared to 19.2% in patients with p-stage II or stage III disease [ 15 ]. Nakamura et al analyzed the frequency of BM as a first relapse site and found a 7% (2/30) BM rate for patients with p-stage I disease, 25% (3/12) for patients with p-stage II SCLC, and 27% (7/26) for patients with p-stage III [ 21 ]. Ogawa et al also reported the frequency of BM, but only 28 patients were included in the study [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of response to chemotherapy on outcome in patients has been demonstrated in the setting of multiple tumors, including rectal, lung, and esophageal, and more recently, with colorectal cancer metastatic to the liver [19][20][21]. In a study by Adam et al the response to chemotherapy was evaluated through imaging studies of abdominopelvic and chest CT scan and abdominopelvic ultrasound utilizing the World Health Organization criteria (WHO) [22].…”
Section: Discussionmentioning
confidence: 99%